PENGARUH JABATAN DAN MUTASI TERHADAP KINERJA KARYAWAN DI PT. PERKEBUNAN NUSANTARA V KEBUN SEI INTAN PEKANBARU RIAU - Eddi Suprayitno; Faisal Ali (JRMB (Jurnal Riset Manajemen & Bisnis), 2019)
This research is to determine the influence of position and mutation of employees ' performance at PT Plantation Nusantara V Sei Intan Pekan Baru Riau.  The samples used in this study were as many as 50 respondents. The data analysis techniques used are qualitative methods, statistical methods using SPSS v 19.0 programs. Primary data collection is conducted through questionnaires distributed to employees of PT Nusantara V Kebun Sei Intan. The method of analysis used is quantitative deskriftif using multiple linear regression. The results proved that the position variables affect positively and insignificant to the employee's performance and the mutation variables are positively and insignificant to the employee's performance, as well as the position and mutation variables Simultaneously positive and significant impact on employee performance. Keywords: job title, mutation, employee performance